Kualitas Hidup Pasien Asma Pengguna Inhaler di Instalasi Rawat Jalan RSUD Sultan Suriansyah: Quality of Asthma Patients’ Life Using Inhalers in The Outpatient Installation of RSUD Sultan Suriansyah - Kamilah, Zahrah; Melviani; Irawan, Angga; Yuwindry, Iwan (Indonesian Journal of Pharmacy and Natural Product, 2023)
Asthma is a heterogeneous disease that can occur in developed and developing countries. The prevalence of asthma in South Kalimantan Province it is 2.8% with a recurrence rate of 55% which is the second highest on the island of Kalimantan. Inhalers are devices used to deliver medication to patients with chronic obstructive pulmonary disease (COPD) and asthma. The quality of life of asthma patients will be worse than normal people. The purpose of the study was to measure the level of quality of life of asthma patients using inhalers in the Outpatient Installation of Sultan Suriansyah Hospital. The method used was descriptive observational with purposive sampling technique using the mini-AQLQ questionnaire. The results showed that of the 83 respondents, the most respondents were asthmatics who were included in the moderate category, namely 61 respondents (73.5%), 16 respondents in the good category (19.3%) and 6 respondents (7.2%) in the bad category. The quality of life of asthma patients using inhalers is more patients who have a quality of life in the moderate category as many as 61 respondents (73.5%) because people pay attention or avoid smoking and dust in their daily lives.   ABSTRAK Asma merupakan penyakit heterogen yang dapat terjadi di negara- negara maju dan berkembang. Prevalensi di Provinsi Kalimantan Selatan sebesar 2,8% dengan tingkat kekambuhannya sebesar 55 % yang menempati posisi tertinggi kedua di Pulau Kalimantan. Inhaler merupakan alat yang digunakan untuk mengantarkan obat pada pasien penyakit paru obstruktif kronis (PPOK) dan asma. Teknik penggunaan inhaler yang buruk dapat meningkatkan resiko eksaserbasi, peningkatan efek samping dan kontrol asma yang buruk. Kualitas hidup pasien asma akan lebih buruk dibandingkan orang normal. Tujuan penelitian untuk mengukur tingkat kualitas hidup pasien asma pengguna inhaler di Instalasi Rawat Jalan RSUD Sultan Suriansyah. Metode yang digunakan yaitu observasional deskriptif dengan teknik pengambilan sampel secara purposive sampling menggunakan kuesioner mini-AQLQ. Hasil penelitian didapatkan bahwa dari 83 responden, responden paling banyak adalah penderita asma yang termasuk kedalam kategori sedang yaitu 61 responden (73,5%), responden dengan kategori baik sebanyak 16 responden (19,3%) dan kategori buruk sebanyak 6 responden (7,2%). Kualitas hidup pasien asma pengguna inhaler di instalasi rawat jalan RSUD Sultan Suriansyah lebih banyak pasien yang memiliki kualitas hidup dengan kategori sedang sebanyak 61 responden  (73,5%) dikarenakan masyarakat memperhatikan atau menghindari rokok dan debu dalam kehidupan sehari-hari.